Mortality and failure among tuberculosis patients who did not complete treatment in Vietnam: a cohort study - Van Le N; Sy Dinh N; Duong Bui D; Huong Nguyen T; Vree Marleen; Co Nguyen V; Cobelens Frank GJ; Borgdorff Martien W (BMC, 2007)
Abstract Background Tuberculosis treatment failure and death rates are low in the Western Pacific Region, including Vietnam. However, failure or death may also occur among patients who did not complete treatment, i.e. reported as default or transfer-out. We aimed to assess the proportion failures and deaths among new smear-positive pulmonary tuberculosis patients with reported default or transfer-out. Treatment outcomes rates were 1.4% default, 3.0% transfer-out, 0.4% failure and 2.6% death in northern Vietnam in 2003. Methods Tuberculosis patients in 32 randomly selected district tuberculosis units in northern Vietnam were followed up 1 to 3 years after treatment initiation for survival, recent treatment history and bacteriologically confirmed tuberculosis. Results Included were 85 transferred patients and 42 who defaulted. No information was available of 41 (32%), 28 (22%) had died. Fifty-eight were available for follow-up (46%); all had sputum smear results. Tuberculosis was recorded in 11 (13%), including 6 (7%) with positive sputum smears, 3 (3%) with negative smears but positive culture and 2 (2%) who had started re-treatment for bacteriologically confirmed tuberculosis. Fifteen (17%, 95%CI 10-27%) had died within 8 months after treatment initiation. Of 86 patients with known study outcomes, 39 (45%, 95%CI 35-56%) had died or had bacteriologically confirmed tuberculosis. This was recorded for 29/53 (55%, 95%CI 40-68%) transferred patients and 10/33 (30%, 95%CI 16-49%) patients who defaulted. Conclusion The total failure and death rates are 0.6% and 0.8% higher than based on routine reporting in northern Vietnam. Although this was a large proportion of treatment failures and deaths, failure and death rates were low. Defaulting and transfer carry a high risk of failure and in particular death.